Inclusivity in stereoscopic XR: Human vision first - Pladere, Tatjana; Svarverud, Ellen; Krumina, Gunta; Gilson, Stuart J.; Baraas, Rigmor C. (Frontiers in Virtual Reality, 2022)
Full accessibility to eXtended Reality Head-Mounted Displays (XR HMDs) includes a requirement for well-functioning eyes and visual system. Eye and vision problems — that affect visual skills and abilities to various degrees — are common and may prevent an individual from comfortably wearing and using XR HMDs. Yet, vision problems have gained little attention in the XR community, making it difficult to assess the degree of accessibility and how to increase inclusivity. This perspective article aims to highlight the need for understanding, assessing, and correcting common eye and vision problems to increase inclusivity — to help broaden a responsible uptake of XR HMDs. There is a need to apply an interdisciplinary, human-centered approach in research. Guidelines are given for conducting reproducible research to contribute to the development of more inclusive XR technologies, through consideration of the individual variations in human visual skills and abilities.